2020
DOI: 10.1002/admi.202000475
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere‐Mediated Scalable and Durable Biphilicity on Rationally Designed Structured Surfaces

Abstract: Biphilic surfaces having spatially distinct wetting have the potential to enable a plethora of applications ranging from fog harvesting, microfluidics, advanced manufacturing, and pumpless fluid transfer. However, complex and costly fabrication along with poor durability have hindered the widespread utilization of biphilic surfaces. Here we demonstrate hierarchical biphilic micro/nanostructured surfaces passively functionalized by the atmosphere as a platform to create scalable and abrasionresistant biphilic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 95 publications
1
15
0
Order By: Relevance
“…Interestingly, the C x H y positive and OH negative ion results for heptane-and octane-exposed surfaces were similar, which indicates that chemisorption of hydrocarbons is likely prior to physisorption at later stages. Previous studies have suggested that VOCs mainly consist of lighter hydrocarbons, which can be both chemisorbed and physisorbed on metallic oxide surfaces (Yan et al, 2019(Yan et al, , 2020. The results presented here confirm this hypothesis.…”
Section: Wettability Transitionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the C x H y positive and OH negative ion results for heptane-and octane-exposed surfaces were similar, which indicates that chemisorption of hydrocarbons is likely prior to physisorption at later stages. Previous studies have suggested that VOCs mainly consist of lighter hydrocarbons, which can be both chemisorbed and physisorbed on metallic oxide surfaces (Yan et al, 2019(Yan et al, , 2020. The results presented here confirm this hypothesis.…”
Section: Wettability Transitionsupporting
confidence: 89%
“…Given the lack of consensus on mechanisms governing REO wettability, a revived interest has developed aimed at understanding how the wettability of solid surfaces exposed to the atmosphere is governed by the physicochemical and electronic properties of the free surface for REOs (Lundy et al, 2017), metals, oxides (Yan et al, 2019(Yan et al, , 2020, and non-metals (Li et al, 2013). In addition to experimental approaches, others have attempted to find evidence to uncover the mechanisms governing wettability using computational methods such as molecular dynamic (MD) simulations.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve highly hydrophilicity, the smooth surfaces were cleaned using air plasma (PDC-001-HP, Harrick Plasma) at a medium power setting for 5-10 min. For all surfaces, the contact angles remained almost unchanged and the effects of adsorption of volatile organic compounds (VOCs) on the surface could be neglected given the short duration of surface atmospheric exposure before and during experiments 32,34 . Table S1 and Section S3 of the Supplementary Information contains detailed characterization of the surfaces.…”
Section: Surface Fabricationmentioning
confidence: 99%
“…In spite of the success of developed laboratory-scale functional surfaces, lack of durability is the primary barrier to dropwise condensation application 28 . Weak adhesion, drainage of the lubricant layer 29 , physical and chemical instability 30,31 , and airborne volatile organic compound deposition [32][33][34] all lead to significant deterioration of condensation performance within short timescales (~weeks). Furthermore, although enhancing droplet shedding is a prevailing strategy to enhance condensation, nucleation site density and condensate morphology play a significant role in determining the overall heat transfer 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Another issue is that the expected wetting properties heavily rely on specific surface morphologies. No matter biomimetic structures (Mele et al, 2012;Barthlott et al, 2010;Schulte et al, 2011;Yi et al, 2019;Kuru et al, 2011;Gao et al, 2005), anisotropic sliding surfaces (Kang et al, 2013;Wu et al, 2011;Zhang et al, 2014), or hierarchical architectures (Yan et al, 2020;Chen et al, 2007;Rykaczewski et al, 2013), they require relatively complicated fabrication steps involving lithography or chemical synthesis, which is challenging for large-area production and seriously restricts their applications.…”
Section: Introductionmentioning
confidence: 99%